(untitled) (Actualizaciones en Sida e Infectología, 2021)
In recent years, new antimicrobials have been developed to combat infections caused by multidrug-resistant microorganism (MDR), including combinations between β-lactam agents (BL) and β-lactamase inhibitors (IBL). Two new combinations of BL / IBL are available in our country: ceftolozano / tazobactam (C / T) and ceftazidime / avibactam (CAZ / AVI). The addition of tazobactam to ceftolozano increases in vitro activity against microorganisms producing extended spectrum BL (ESBL), so the combination has a potent intrinsic activity against P. aeruginosa. For its part, CAZ / AVI retains the characteristics that define the activity profile of ceftazidime, to which with the addition of avibactam it presents a potent inhibitory activity against ESBL and carbapenemases (KPC, β-lactamases of class C and some of class D). A review of the published evidence is presented below. Based on this, and considering the current situation of increasing rates of antimicrobial resistance, particularly in Gram-negative bacilli, we consider that the use of C/T or CAZ/AVI is an excellent alternative for the management of serious infections caused by multi-resistant microorganisms. However, its use empirically is not recommended, except in specific and strictly selected situations, and in the context of a program for the rational use of antibiotics, under the control of the responsible infectious disease team.